A PHENOMENOLOGICAL APPROACH TO THE STUDY OF SOCIAL-PSYCHOLOGICAL LONELINESS AMONG STUDENTS - E. Filindash (Вестник университета)
The article is devoted to the problem of social-psychological loneliness among students. The phenomenology of loneliness is represented in the totality of the definition study the definition, causes, structure, typology. The work is based on empirical material, presents the results of a poll conducted among the students of Moscow universities.